Bitter reckoning : Israel tries Holocaust survivors as Nazi collaborators - Porat, Dan 1964- (The Belknap Press of Harvard University Press, 2019)
From revenge to retribution in post-Nazi Europe -- Tensions among survivors in mandatory Palestine -- The Nazis and Nazi Collaborators Punishment Law -- Preliminary court examinations -- Weighing the actions of Jewish collaborators -- Can a Jewish kapo commit a crime against humanity? -- The first doubts about the kapo trials -- Judging a Nazi and reframing collaboration -- Absolving ordinary functionaries.